Analysis of the economic and environmental efficiency of ecological bags in the production of the commercial sector of the department of Cesar - Arévalo - Arévalo, Breiner José; Caviedes - Noriega, Vanesa Alexa (Universidad Francisco de Paula Santander, 2021)
Plastic bags are a product consumed and distributed in society by the commercial sector and constitute an important source in the economy, but at the same time it is highly polluting. Given this, in 1965 Sten Gustaf Thulin created ecological bags as a mitigation and replacement strategy for plastic bags. For this reason, this study focused on analyzing the economic and environmental efficiency of ecological bags in the production of the commercial sector of the Cesar department. A qualitative methodology with a descriptive scope was used. The technique used for data collection was a documentary review, doing a bibliometric analysis with Scopus and academic Google databases. The analysis will focus on analyzing the environmental and economic profitability of replacing polyethylene plastic bags with reusable ecological ones, mitigating the impact on the environment, without affecting the budget of citizens.